Promoting a culture of respect in cardiothoracic surgery: navigating challenges in understanding unethical behaviour - A.Yu. Sydorenko; H. Spindler (Medičnì Perspektivi)
Unprofessional behaviour in the workplace, such as bullying, harassment, and discrimination, remains common in the cardiothoracic surgery unit. Despite its prevalence, there is little consensus on what constitutes unprofessional behaviour in the workplace of a cardiothoracic surgeon. In this review, we aim to narrow down the definition of unprofessional behaviour among cardiothoracic surgeons, identify its prevalence and the factors contributing to it, as well as explore potential preventive and support measures. We searched the MEDLINE and Web of Science databases (2000-2022), focusing on publications within psychology, medicine, general surgery, and cardiothoracic surgery for inclusion in a focused review. The current review identified 89 papers that highlight the complexity of defining unprofessional behaviour and its prevalence in cardiothoracic surgery units. Psychosocial professional challenges, hierarchical relationships within the medical team, and a high-stress environment may prompt unprofessional behaviour, which can manifest in both overt and covert actions. Such behaviour negatively mpacts medical services for patients, the psycho-emotional state of employees, and the overall functioning of the medical institution. The most effective support measures are characterized by being proactive, anticipating potential problems before they occur. Unprofessional behaviour should be considered an organizational concern, not merely an issue between individual team members. This perspective is essential for fostering a healthy work environment. The leaders of cardiothoracic surgery, given their high status and authority, play a pivotal role in this regard; their focus on inclusiveness of employees with lower status or responsibility is crucial for promoting a culture of psychosocial safety. This culture should be characterized by trust, honesty, and mutual respect, ensuring that every team member feels valued and respected. By prioritizing these values, leaders can minimize the risk of unprofessional behaviour, ultimately leading to an improvement in the quality of medical services for patients, an improvement in the psycho-emotional state of employees and the functioning of the organization as a whole.